In Memoriam Prof. Ryszard Pęcherski, 1949–2022 - NOWAK, Zdzisław; KOWALCZYK-GAJEWSKA, Katarzyna; NOWAK, Marcin; SZEPTYNSKI, Paweł (Engineering Transactions, 2023)
Ryszard Bolesław Pęcherski was born on March 15, 1949 in Stopnica closely to the town Busko-Zdrój in Poland and passed away in Warsaw on December 22, 2022. He graduated from Gdansk University of Technology in 1973. In in October of 1974 he began doctoral studies at the Institute of Fundamental Technological Research of the Polish Academy of Sciences (IPPT PAN) in Warsaw, which he completed in 1978. Shortly after his doctoral studies, in 1979 as assistant professor he went abroad for a one-year scholarship at the Tohoku University in Sandai, Japan. In the years 1983–1987 he worked as a scholarship recipient of the Alexander von Humboldt Foundation at the University of Hanover in the Institut für Baumechanik und Numerische Mechanik and as a six months scholarship recipient of the DAAD in Technische Hochschule in Holzminden. Before defending his dissertation, he was employed at IPPT PAN first in the Laboratory of Theory of Viscoplasticity in the Department of Mechanics of Continuum, and then in the Division of Theory of Inelastic Materials. In 1998, he completed his Habilitation thesis, for which he received a degree of habilitated doctor in mechanics. The title of Associate Professor was conferred on him in 1999. In 2000 he was employed in the Department of Strength of Materials of the Institute of Structural Mechanics at the Cracow University of Technology. He gave lectures on the subject Strength of Materials. In 2007 he received the title of professor and in the same year he finished his work at the Cracow University of Technology. He continued his scientific and didactic activity at the Department of Strength and Fatigue of Materials and Structures of the AGH University of Science and Technology in Cracow.In 2009, Prof. Ryszard Pęcherski was the head of the Laboratory of Applied Plasticity at the Department of Mechanics of Materials IPPT PAN, and in years 2017–2020 he was the head of the Department of Theory of Continuous Media and Nanostructures, IPPT PAN. In years 2020–2022 he was the deputy manager in the Department of Theory of Continuous Media and Nanostructures and leader of the Division of Polymer Physics. In 2009, Prof. Ryszard Pęcherski was the head of the Laboratory of Applied Plasticity at the Department of Mechanics of Materials IPPT PAN, and in years 2017–2020 he was the head of the Department of Theory of Continuous Media and Nanostructures, IPPT PAN. In years 2020–2022 he was the deputy manager in the Department of Theory of Continuous Media and Nanostructures and leader of the Division of Polymer Physics. The Professor Pęcherski scientific activity concerned various aspects of the mechanics of materials. Over time, the subject of research has been extended to the mechanics of anisotropic, nanostructures, cellular and composite materials. He was interested in the problems of energy limit state criteria for anisotropic materials with an asymmetric elastic range, material effort hypotheses for cellular materials, flexible adhesive joints, multi-scale modelling, mechanics of ceramic-metal composites. He was the principal investigator of many research projects and the author of several dozen scientific publications.